Bayesian Network Approach in Educational Application Development: A Systematic Literature Review and Bibliometric Meta-Analysis - Chanthiran, Maran; Ibrahim, Abu Bakar; Abdul Rahman, Mohd Hishamuddin; Mariappan , Punithavili (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Technological developments have brought about a paradigm shift in the world of education. The education system must be more open and flexible, where students can experience these opportunities according to their skill level. 21st-century education and the application of the elements of Revolution 4.0 Industry in education realize that initiative. The Bayesian Network approach is becoming one of the essential tools in the development of educational applications. Therefore, the persistence of this systematic review is to identify peer-reviewed literature on the Bayesian network approach in education. Scopus and Web of Science, and IEEE citation databases are used in the data-gathering phase. PRISMA approach and keyword search were obtained and analyzed. This bibliographic data of articles published in the journals over ten years were extracted. VOS viewer was used to analyzing the data contained in all journals and articles. This systematic review shows that the development in education can absorb the changes that occur in technology. The findings from 1160 articles extracted show that using the Bayesian approach in the development of educational applications improves the quality of use, especially from the point of students. The level of predictive accuracy generated through the Bayesian network approach improves the quality of educational application development. However, the study's findings indicate that there is scope for research related to the application and use of this approach in the development of educational applications.